Quantitative Analysis of Eight Triterpenoids and Two Sesquiterpenoids in Rhizoma Alismatis by Using UPLC-ESI/APCI-MS/MS and Its Application to Optimisation of Best Harvest Time and Crude Processing Temperature - Yanni Tai; Fuxian Zou; Qiurong Zhang; Jia Wang; Ronghui Rao; Ruihua Xie; Shuisheng Wu; Kedan Chu; Wen Xu; Xiaoyan Li; Mingqing Huang (Journal of Analytical Methods in Chemistry)
Rhizoma Alismatis (RA), widely known as “Ze-Xie” in China, is the tuber of Alisma orientale (Sam.) Juzep (Alismaceae), a Chinese herbal medicine that has been used to treat hyperlipidemia, diabetes, hypertension, dysuria, and inflammation. In this study, a sensitive and reliable method based on an ultra-performance liquid chromatography (UPLC) couple with two ionisation modes, including electrospray ionisation (ESI) and atmospheric pressure chemical ionisation (APCI) tandem mass spectrometry (MS), namely, UPLC-ESI/APCI-MS/MS was developed and validated to simultaneously determine 8 triterpenoids (ESI mode) and 2 sesquiterpenoids (APCI mode) in RA. Ten marker compounds were analysed with a Waters’ CORTECS UPLC C18 column (200 mm × 2.1 m, 1.6 μm) and gradient elution with water (contained 0.1% formic) and acetonitrile within 7 min. The established method was validated for linearity, intra- and interday precisions, accuracy, recovery, and stability. The calibration curve for 10 marker compounds showed good linear regression (r > 0.9971). The limits of detection and quantification for analytes were 0.14–1.67 ng/mL and 0.44–5.65 ng/mL, respectively. The relative standard deviations (RSD, %) and accuracy (RE, %) of intra- and interday precisions were less than 3.83% and 1.21% and 3.22% and 1.46%, repeatability and stability for real samples were less than 2.78% and 3.19%, respectively. All recoveries of the 10 marker compounds ranged from 97.24% to 102.49% with RSDs less than 4.05%. The developed method efficiently determined the 10 marker compounds in RA and was subsequently applied to optimise harvest time and crude processing temperature. The result indicated the 90% wilted phase and 70°C (or lower) may be the best harvest time and the processing temperature of RA.